1990
DOI: 10.1111/j.1399-3054.1990.tb04381.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biosynthesis in seeds of mustard (Brassica juncea) influenced by zinc and sulphur deficiency

Abstract: In developing seeds of mustard (Brassica juncea L. cv. RLM 198) the period between 20 and 30 days after fertilization (DAF) was identified as the period of active lipid biosynthesis, although dry matter continued to accumulate until maturity. The period of lipid synthesis was associated with a decrease in starch, soluble sugars and protein, thus, giving rise to precursors for the biosynthesis of lipids. Besides decreasing the dry matter content (on both % and seed basis), Zn and S deficiency caused a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
4
10
0
Order By: Relevance
“…Irrespective of the treatments, total sugar content started decreasing from 10 DAF until harvest (HR). These findings agree with some earlier studies in oilseed crops (Ahmad et al 2000;Fazli et al 2005a;Munshi et al 1990). Application of S (T2) increased the total sugar content at all the stages of seed development compared to -S treatment (T1).…”
Section: Resultssupporting
confidence: 95%
See 3 more Smart Citations
“…Irrespective of the treatments, total sugar content started decreasing from 10 DAF until harvest (HR). These findings agree with some earlier studies in oilseed crops (Ahmad et al 2000;Fazli et al 2005a;Munshi et al 1990). Application of S (T2) increased the total sugar content at all the stages of seed development compared to -S treatment (T1).…”
Section: Resultssupporting
confidence: 95%
“…Irrespective of the treatments, oil accumulation in the seeds commenced at 10 DAF and continued till 30 DAF, beyond which no significant increase was observed. These findings are in agreement with some earlier studies in oilseeds (Abdin et al 2003; Ahmad and Abdin 2000a; Ahmad et al 2000;Chung et al 1995;Fazli et al 2005a,b;Munshi et al 1990;Turnham and Northcote 1983;Weselake et al 1993). Sulphur application (T2) increased the oil accumulation at all stages of seed development compared to -S+N treatment (T1).…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…This result might be due to increased activities of α-and β-amylases in the former positions (data not shown). The accumulation of starch in sunflower 7 and other oilseeds 6,9,10 during seed development has already been well documented, and this starch is known to serve as a transient reserve material for the synthesis of storage lipids, ie triacylglycerols. Our recent study has shown that starch synthesis is biphasic in the seeds in the peripheral whorls in comparison with those in the middle and central whorls of the sunflower head, 11 which might contribute to better utilisation of starch for lipid biosynthesis.…”
Section: Resultsmentioning
confidence: 99%